The Effect Of Kasti Ball Game On The Improvement Of Positive Cultural Characters In Grade 5 Students Of State Elementary School 35 Krui, Ngaras District - Putra, Yuda Gastriana; Susilawati, Dewi (Sains Global Institut, Indonesia, 2024)
This study aims to examine the effect of playing baseball on improving positive cultural character in 5th grade elementary school students. The method used is quantitative with an experimental design. The research sample consisted of 20 students divided into two groups: an experimental group that participated in playing baseball and a control group that did not. The results showed that there was a significant increase in the positive cultural character of students involved in playing baseball, with a p value <0.05. This study concludes that playing baseball can be an effective tool in forming positive cultural character in students